توظيف الإمام النووي تفسير القرآن في شرح الحديث في شرحه لصحيح مسلم ـ دراسة نظرية تطبيقية ـ Employing Imam Al-nawawi The Interpretation Of The Holy Qur-an In Explaining The Hadith In His Explanation Of Sahih Muslim -an Applied Theoretical Study - بوجاجة بلقاسم; رمضاني محمد (University of Eloued جامعة الوادي, 2023)
يهدف البحث لبيان العلاقة بين شرح الحديث النبوي، وتفسير القرآن الكريم، من خلال البحث في توظيف كلام المفسرين في شرح الحديث النبوي، ولمعرفة ذلك نبحث في مدى رجوع الإمام النووي إلى كتب التفسير في شرحه لصحيح مسلم، وكيف استعان الإمام النووي في شرحه للحديث بكلام المفسرين في تفسيرهم للقرآن الكريم، وبيان منهج الإمام النووي في الاستفادة من كلام المفسرين في شرح الحديث وسياق ذلك، مع إبراز ذلك بنماذج تطبيقية من شرح الامام النووي لصحيح مسلم، وأقدم للبحث بمقدمة نظرية أعرف فيها بشرح الحديث النبوي، وكذا تفسير القرآن الكريم، والعلاقة بين تفسير القرآن الكريم وشرح الحديث النبوي، ومن خلال البحث وقفنا على توظيف الإمام النووي كلام المفسرين في شرح الكثير من الأحاديث، واختلفت أغراضه في ذلك فقد يستعين به في شرح الألفاظ، أو لبيان أسباب النزول، وكذا في شرح الأحاديث التي تناولت قصصا اشرك القرآن والحديث في ذكرها، وغير ذلك. The research aims to clarify the relationship between the explanation of the hadith of the prophet and interpretation of the holy Qur-an depending on the employment the words of the interpreters in explaining the hadith of the prophet, In order to know this we have to examine the extent to which Imam al-Nawawi referred to the books of interpretation in his explanation of sahih muslim, In my research a theoretical introduction through which I define the explanation of the prophet's hadith as Well as the interpretation of the holy Qur-an highlighting the relationship between the interpretation of the holy Qur-an and the explanation of the prophet's hadith and through my research I indicated that Imam al-Nawawi used the words of the interpreters to explain many of the hadiths and his purposes differed in that using him to explain the words or to explain the reasons for the revelation as Well as in explaining the hadiths that dealt with stories that the holy Qur-an and the hadith participated in mentioning
Keywords: شرح الحديث; تفسير القرآن الكريم; شرح صحيح مسلم; الامام النووي; Explanation of the hadith; Interpretation of the holy Qur-an; Imam al-Nawawi; Explanation of sahih muslim